Stress and addiction: contribution of the corticotropin releasing factor (CRF) system in neuroplasticity - Haass-Koffler, Carolina L.; Bartlett, Selena E. (Frontiers in Molecular Neuroscience, 2012)
Corticotropin releasing factor (CRF) has been shown to induce various behavioral changes related to adaptation to stress. Dysregulation of the CRF system at any point can lead to a variety of psychiatric disorders, including substance use disorders (SUDs). CRF has been associated with stress-induced drug reinforcement. Extensive literature has identified CRF to play an important role in the molecular mechanisms that lead to an increase in susceptibility that precipitates relapse to SUDs. The CRF system has a heterogeneous role in SUDs. It enhances the acute effects of drugs of abuse and is also responsible for the potentiation of drug-induced neuroplasticity evoked during the withdrawal period. We present in this review the brain regions and circuitries where CRF is expressed and may participate in stress-induced drug abuse. Finally, we attempt to evaluate the role of modulating the CRF system as a possible therapeutic strategy for treating the dysregulation of emotional behaviors that result from the acute positive reinforcement of substances of abuse as well as the negative reinforcement produced by withdrawal.